Comment on "Evaluating Recipes for Development Success" - Keefer, Philip (World Bank, 2012)
Two arguments are important: that the rule of law and the security of property rights are important for growth and that they are the product of political institutions. Professor Dixit argues that identification and other concerns undermine the second argument and inhibit the formulation of policy recommendations. Avinash Dixit reviews many of the recent contributions to the literature that examine the "big" questions in economic development, particularly those concerning the fundamental differences between countries that manage to sustain rapid economic growth and those that do not. Practitioners can nevertheless learn from the generalizations that academic research yields, but they should examine the plausibility of those generalizations, taking into account the many idiosyncrasies The Author 2007. These are based on particular historical and geographic features of countries that researchers theorize should determine the security of property rights but that should not directly affect growth. Just as important, compared with such determinants of political behavior as history and regime type, theses sources of variation in political incentives have at least somewhat more tractable policy implications for what donors and governments should and should not do. Incremental approaches that fail to take the conditions of political decision-making into account in a systematic way are no more likely to succeed than "maximalist" approaches. Less targeted programs, in which targeting is crude but easy to communicate and simple to implement, may offer a greater contribution to development by building political credibility, even at the cost of economic inefficiency. From the first Public Expenditure Tracking Philip Keefer 163 Survey in Uganda, which led to a 90 percent reduction in the diversion of capitation grants to schools, to report cards on public services, pioneered in Bangalore, India, but expanding to China and elsewhere, a variety of tactics are emerging to close the information gap between citizens and politicians. Despite this--despite the fact that such analyses are concerned with big ideas--this line of research shows considerable promise in informing both the content and the design of the reform agenda in countryspecific contexts.